Digital Media as English Language Learning Facilities and Infrastructure - Ummu Mulkiyah (English Education Study Program, 2023)
Technological developments in the era of the industrial revolution 4.0 affect everything, including the education sector. The national education sector must be ready for major changes in the face of current technological developments. MTs Nurul Qomar Tawangrejo are very supportive of utilizing digital media as English language learning so that they provide complete facilities and infrastructure, especially internet access as a major component in the sustainability of digital-based learning. With the complete facilities and infrastructure, it makes it easy for teachers and students to do learning. This research uses a qualitative descriptive method, data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The purpose of this research was to find out and analyze the utilization of digital media as English language learning facilities and infrastructure at MTs Nurul Qomar Tawangrejo. After adapting to distance learning which uses digital media, it has now become commonplace and even makes it easier for teachers to carry out the learning process, so MTs Nurul Qomar Tawangrejo is increasingly maximizing the utilization of digital media as English language learning facilities and infrastructure. Through digital media, it can provide various facilities for teachers and students to carry out learning.